2013
DOI: 10.1158/0008-5472.can-12-4039
|View full text |Cite
|
Sign up to set email alerts
|

The MET Oncogene in Glioblastoma Stem Cells: Implications as a Diagnostic Marker and a Therapeutic Target

Abstract: The MET oncogene, a crucial regulator of the genetic program known as "invasive growth" or "epithelialmesenchymal transition," has recently emerged as a functional marker of glioblastoma stem cells. Here, we review findings that associate MET expression and activity with a specific, genetically defined glioblastoma stem cell subtype, and data showing how MET sustains the stem cell phenotype in glioblastoma and other tumors. Finally, we discuss issues related to identification of tumorigenic clones driven by ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 51 publications
2
49
0
Order By: Relevance
“…YKL-40 expression associated with the lack of EGFR amplification oriented to mesenchymal profile; moreover, lack of MGMT promoter methylation and presence of IDH1 S surgery: 0=exeresis, 1=biopsy, 1*=only autoptic diagnosis, RT radiotherapy: 0=no, 1=yes, CT chemotherapy: 0=no, 1=yes (only alkylant), 2=alkylant + molecular therapy, D-D brain GBM diagnosis-death, D-M brain GBM diagnosis-metastases onset, uk unknown wild type are concordant with the observation that mesenchymal is not associated with the hypermethylation phenotype [5]. c-Met can be expressed in pro-neural and mesenchymal phenotypes [7] and is potentially involved into the acquired BV resistance [39]. In both our cases, MET protein was not expressed.…”
Section: Discussionsupporting
confidence: 62%
“…YKL-40 expression associated with the lack of EGFR amplification oriented to mesenchymal profile; moreover, lack of MGMT promoter methylation and presence of IDH1 S surgery: 0=exeresis, 1=biopsy, 1*=only autoptic diagnosis, RT radiotherapy: 0=no, 1=yes, CT chemotherapy: 0=no, 1=yes (only alkylant), 2=alkylant + molecular therapy, D-D brain GBM diagnosis-death, D-M brain GBM diagnosis-metastases onset, uk unknown wild type are concordant with the observation that mesenchymal is not associated with the hypermethylation phenotype [5]. c-Met can be expressed in pro-neural and mesenchymal phenotypes [7] and is potentially involved into the acquired BV resistance [39]. In both our cases, MET protein was not expressed.…”
Section: Discussionsupporting
confidence: 62%
“…Besides hypoxia-driven, HIF2A-controlled differentiation processes, we found that miR-182 also regulates glioma cell growth by targeting the RTK c-Met, which represents a functional glioma stem cell marker and promoter of GIC self-renewal (Boccaccio and Comoglio 2013). A survey of the TCGA data set showed a prominent negative correlation between miR-182 and c-Met mRNA expression, predominantly in classical and proneural GBM tumors (Fig.…”
Section: Mir-182 Regulates C-met-controlled Glioma Cell Growthmentioning
confidence: 84%
“…There has been a report that stemness transcription factor OCT4 positively regulates BCRP/ABCG2 expression in chronic myeloid leukemia (Marques et al, 2010). Furthermore, lines of evidence have shown that c-MET is involved in the maintenance of cancer stem cell phenotypes (Boccaccio and Comoglio, 2013). These studies suggest that the increase in c-MET-mediated stemness markers may be associated with BCRP overexpression.…”
Section: Role Of C-met/bcrp Signaling In Cancer Resistancementioning
confidence: 94%